Per- and polyfluoroalkyl substances in feathers of waterbirds (Ardeidae) from Poyang Lake, China: Bioaccumulation, distribution, and environmental relevance - Nannan Wan; Bo Zhou; Limin Mo; Qiyu Wang; Shuai Liu; Miao Zhang; Yu Liu; Xiaojun Luo; Bixian Mai (Journal of Hazardous Materials Letters)
Studies on the distribution characteristics and environmental relevance of per- and polyfluoroalkyl substances (PFAS) in waterbird feathers are scarce. In the present study, the concentrations of twenty-three PFAS in the remiges, coverts, body, down, and tail feathers of three common species of Ardeidae (little egret, grey heron, and Chinese pond-heron) in Poyang Lake were investigated. The total PFAS concentrations in the pinna and scapus were 38 – 42 ng/g dry weight (dw) and 21 – 38 ng/g dw, respectively; long-chain C9–14 perfluorocarboxylic acids were abundant in all feathers. Most PFAS accumulated in the pinna; however, perfluorohexane sulfonic acid and perfluorooctane sulfonamide were predominant in the scapus. The PFAS concentrations were higher in the tail and flight feathers than in the cover and body feathers. Furthermore, the concentrations of PFAS in waterbird feathers were comparable with those in fish and higher than those in benthic invertebrates, all of which originated from Poyang Lake. The PFAS profiles in feathers were significantly and positively correlated with those in fish (r > 0.71) and benthos (r > 0.43). These results suggest that waterbird feather is a suitable biomonitor of PFAS contamination in regional freshwater ecosystems.